Poor nutritional status and growth retardation are associated with living in the orphanage: an observational cross-sectional study - Seremet Kürklü, Nilgün; Tel Adıgüzel, Kübra; Ede, Gözde; Samur, Gülhan (Progress in Nutrition, 2022)
Objective: Adequate and balanced nutrition is crucial for optimal growth and development. However, children living in orphanages without a family are at risk of malnutrition. In this study, we aimed to compare the nutritional status and growth process of orphans and non-orphans. Methods: We recruited 111 orphans and 116 non-orphans aged 3-6 years. We excluded children with any acute or chronic disease and physical or mental problems. We assessed dietary intakes via the 3 days food record form. We took anthropometric measurements and evaluated the growth level of children using the Z-score tables of the World Health Organization.  We analyzed the data using IBM SPSS. Results: Of the 227 children, the prevalence of undernutrition was as high as 54.8% among children in the orphans. According to Z-score of height for age values, 23.4% of orphans were only 4.3% of non-orphans were stunted. While the mean energy intake was significantly higher in orphans compared to non-orphans (1802.7±552.80 kcal vs. 1480.8±244.53 kcal, p